2005
DOI: 10.1152/ajpcell.00362.2003
|View full text |Cite
|
Sign up to set email alerts
|

Force transmission, compliance, and viscoelasticity are altered in the α7-integrin-null mouse diaphragm

Abstract: Alpha7beta1 integrin is a transmembrane structural and receptor protein of skeletal muscles, and the absence of alpha7-integrin causes muscular dystrophy. We hypothesized that the absence of alpha7-integrin alters compliance and viscoelasticity and disrupts the mechanical coupling between passive transverse and axial contractile elements in the diaphragm. In vivo the diaphragm is loaded with pressure, and therefore axial and transverse length-tension relationships are important in assessing its function. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 43 publications
(40 reference statements)
2
26
0
Order By: Relevance
“…␣ 7 ␤ 1 -Integrin is a transmembrane structural protein concentrated at the MTJ, linking to actin cytoskeleton through talin/vinculin. Alterations in compliance have been observed in ␣ 7 -integrin (Itga7) knockout mouse muscle (38), consistent with the possibility of the ␣ 7 ␤ 1 -integrin being a load-bearing protein. In our previous yeast two-hybrid study, we showed that mXin␣ interacted with vinculin and filamin (10).…”
Section: Discussionsupporting
confidence: 66%
“…␣ 7 ␤ 1 -Integrin is a transmembrane structural protein concentrated at the MTJ, linking to actin cytoskeleton through talin/vinculin. Alterations in compliance have been observed in ␣ 7 -integrin (Itga7) knockout mouse muscle (38), consistent with the possibility of the ␣ 7 ␤ 1 -integrin being a load-bearing protein. In our previous yeast two-hybrid study, we showed that mXin␣ interacted with vinculin and filamin (10).…”
Section: Discussionsupporting
confidence: 66%
“…Reduced compliance was also observed in diaphragm muscle from 1-year-old ␣7 integrinnull mice. 32 Changes in the deposition and/or composition of extracellular matrix or expression of the repertoire of integrins in vascular smooth muscle may contribute to this phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the ␣7-integrin gene are responsible for human congenital myopathy, in which patients exhibit delayed motor milestones (Hayashi et al, 1998). Mice that lack ␣7 integrin develop myopathy and demonstrate altered force transmission, compliance and viscoelasticity in diaphragm muscle (Lopez et al, 2005;Mayer et al, 1997). In addition, ␣7␤1 integrin plays an important role in the development of NMJs (Burkin et al, 1998;Burkin et al, 2000) and MTJs (Mayer et al, 1997;Nawrotzki et al, 2003).…”
Section: Introductionmentioning
confidence: 99%